Exploratory analysis of the key role of immune function changes in BPD - Tianyi Wu; Xingmeng Fu; Xiaoxia Gong; Jingyi You; Zhou Fu; Chang Shu (Pediatric Discovery)
Abstract Bronchopulmonary dysplasia (BPD) is one of the most prevalent and severe chronic lung diseases in premature infants. The objective of the current study was to screen for key BPD‐associated genes and pathways by transcriptomic analysis from clinical patients and animal models. In our study, the differentially expressed genes were screened from 58 children with 14‐day BPD and 40 normal children in the GSE32472 dataset of the Gene Expression Omnibus database. Then, we identified four hub genes (Cd3e, Cd3g, Cd247, and Itk) and a signaling pathway (T cell receptor signaling pathway) by Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathway enrichment analysis and protein‐protein interaction analysis. The differential expression of the relevant pathways and gene sets among the groups was verified via GSEA analysis. Subsequently, a rat model of BPD with hyperoxia‐induced lung injury was established, and the transcriptome sequencing of the whole lung tissue was performed. A similar analysis was done on the sequencing data of the hub genes and associated pathway screening to verify the accuracy. Ultimately, quantitative polymerase chain reaction was performed to validate the transcriptomics data of core gene expression in the rat model. Our study revealed that the downregulation of the expression of the above four key genes in the course of BPD leads to a decrease in the function of T cell receptor signaling pathways, it causes immune dysfunction and increases the severity of lung inflammation as well as susceptibility to other respiratory infectious diseases.